If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(p + -4) = 2(p + 1) Reorder the terms: 3(-4 + p) = 2(p + 1) (-4 * 3 + p * 3) = 2(p + 1) (-12 + 3p) = 2(p + 1) Reorder the terms: -12 + 3p = 2(1 + p) -12 + 3p = (1 * 2 + p * 2) -12 + 3p = (2 + 2p) Solving -12 + 3p = 2 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -12 + 3p + -2p = 2 + 2p + -2p Combine like terms: 3p + -2p = 1p -12 + 1p = 2 + 2p + -2p Combine like terms: 2p + -2p = 0 -12 + 1p = 2 + 0 -12 + 1p = 2 Add '12' to each side of the equation. -12 + 12 + 1p = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 1p = 2 + 12 1p = 2 + 12 Combine like terms: 2 + 12 = 14 1p = 14 Divide each side by '1'. p = 14 Simplifying p = 14
| 1.5v-0.9v+2.5=4.5 | | 9x+x-4x=24+48 | | -7(n-3)=-7n+21 | | 7-2n=8n-(4n) | | 4x-4=6x+5 | | (9/7)(7/16)=x | | 6z+6z=7z-2-5z | | (.01)(.3)= | | -9(m+5)-2(9m+7)=-28(m+3)-2 | | 1.5*x=60 | | 1+2v=9+3v | | P(x)=10*7-7 | | 5a+3=-22 | | 8(2n+3)=9(7n+2+3) | | x*8=72 | | 0=16t^2-24t+20 | | -3y-10=7y+10 | | P(x)=10*10-7 | | -2(t-2)+9t=3t-4 | | -9=12y+3 | | 7x+3=-8+3x+23 | | 18=7b+4 | | -9-4= | | 5p-14=26 | | 6-6(a+2)=8+a | | A+1.5=6 | | 1.7x=5.61 | | x^2=650 | | -(-5-6)=4(5x+3) | | P(x)=x(50x^2+30x)-90 | | -2(t-1)+4t=6t-6 | | P(x)=x(50x^2+30x) |